2023
DOI: 10.1128/jb.00138-23
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate enhances Clostridioides difficile sporulation in vitro

Michelle A. Baldassare,
Disha Bhattacharjee,
Julian D. Coles
et al.

Abstract: Short-chain fatty acids (SCFAs) are products of bacterial fermentation that help maintain important gut functions such as maintenance of the intestinal barrier, cell signaling, and immune homeostasis. The main SCFAs acetate, propionate, and butyrate have demonstrated beneficial effects for the host, including its importance in alleviating infections caused by pathogens such as Clostridioides difficile . Despite the potential role of SCFAs in mitigating C. difficile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…S16d-e Certain bacteria in the gut have been reported to increase C. difficile toxin production and enhance their fitness and virulence in vivo, such as the opportunistic pathogen Enterococcus faecalis 70 . Some metabolites produced by gut microbes such as butyrate could also increase C. difficile toxin, albeit moderately 85 . However, we found that the enhancement of C. difficile toxin is sparse among human gut commensals (toxin production per unit biomass is enhanced in only ~16% of all communities compared to monocultures).…”
Section: Discussionmentioning
confidence: 99%
“…S16d-e Certain bacteria in the gut have been reported to increase C. difficile toxin production and enhance their fitness and virulence in vivo, such as the opportunistic pathogen Enterococcus faecalis 70 . Some metabolites produced by gut microbes such as butyrate could also increase C. difficile toxin, albeit moderately 85 . However, we found that the enhancement of C. difficile toxin is sparse among human gut commensals (toxin production per unit biomass is enhanced in only ~16% of all communities compared to monocultures).…”
Section: Discussionmentioning
confidence: 99%